Karewsky syndrome: A case report and review of the literature - Ploneda-Valencia, César Felipe (Int J Surg Case Rep, 2015)
INTRODUCTION: Gallstone ileus can be a lethal disease, rarely suspected in the clinical scenario. It represents about 25% of all bowel obstruction cases in patients older than 65. There is a classification of gallstone ileus based on the onset time: acute, subacute and chronic (Karewsky syndrome). We describe the first reported case of chronic gallstone ileus. CASE PRESENTATION: A 78-year-old female was admitted to the ER with a 15-day case of consistent bowel obstruction. The subject reported a five-year history of recurrent hospital admissions that resolved spontaneously after non-surgical management. Karewsky syndrome was diagnosed and managed with enterolithotomy. After five days of postoperative evolution the patient was discharged, and at six months follow up, no other hospital admission or relapse has been registered. DISCUSSION: The gallstone ileus diagnosis demands a higher clinical suspicion, there is no biochemical marker, and an abdominal CT is ideal for imaging-based diagnosis. There is no consensus on the optimal surgical approach. CONCLUSION: We describe the first case of Karewsky syndrome and a gastro-jejune and gastric-choledochus double fistula. We emphasize the importance of higher clinical suspicion for patients with bowel obstruction older than 65 years old and make evident that although there are not evidence-based guidelines for this treatment, enterolithotomy is a recommended approach.